Photovoltaic module gap synergistic film and preparation method and application thereof

By using gap-enhancing films containing activateable materials and reflective fillers in photovoltaic modules, the problem of deterioration of the adhesive effect of the positioning tape and insufficient reflection effect is solved, and higher adhesive performance and reflectivity are achieved, and the remediation is carried out. The film is tear off without loss, improving the overall performance and recycling efficiency of photovoltaic modules.

CN119119893APending Publication Date: 2024-12-13KOLESI TECHNOLOGY (WUXI) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411247465.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The positioning and bonding effect of existing photovoltaic module positioning tapes deteriorate during lamination, resulting in the disassembly of the battery and displacement, and are not easy to tear off from the battery, affecting rework and recycling, and lack of reflection effects affecting the performance of the component.

Method used

A photovoltaic module gap synthesis film including an adhesive layer and a functional layer is a pressure-sensitive adhesive layer containing an activateable material, and the functional layer is an ethylene copolymer containing a melting point of 70-120°C, and is subject to incomplete coating. The fabric structure and activation materials such as tert-butoxycarbonyl acrylate polymers provide strong bonding and tear-free properties, and the addition of reflective fillers to the composite substrate layer increases reflectivity.

Benefits of technology

The positioning and adhesive performance and reflectivity of photovoltaic modules are improved, the overall improvement of component performance is ensured, and the efficiency enhancement film is removed from the battery during rework to avoid damage and enhance the absorption and transmission efficiency of light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005031223940000161
    Figure BDA0005031223940000161
  • Figure BDA0005031223940000171
    Figure BDA0005031223940000171
Patent Text Reader

Abstract

The invention provides a photovoltaic module gap synergistic film and a preparation method and application thereof.The photovoltaic module gap synergistic film comprises a bonding layer, a functional layer and a composite base material layer are sequentially arranged on the bonding layer from bottom to top, the bonding layer is a pressure-sensitive adhesive layer containing an activatable material, and the functional layer is a functional layer containing an ethylene copolymer with the melting point ranging from 70 DEG C to 120 DEG C; therefore, not only are the positioning bonding performance and the reflectivity of the product improved, but also the overall performance of the photovoltaic module is ensured, and meanwhile, the gap synergistic film of the photovoltaic module is torn off from the battery in a lossless manner so as to repair or recycle the photovoltaic battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photovoltaic modules, and in particular to a photovoltaic module gap enhancement film and a preparation method and application thereof. Background Art

[0002] Photovoltaic modules are made of photovoltaic glass, packaging materials, batteries, backplane (or glass) and other layers, which are put into the photovoltaic laminator and laminated under the lamination conditions of 120-150℃. During the lamination process of the modules, positioning tape is required to fix the battery string to prevent problems such as paralleling of battery cells and displacement between strings.

[0003] The structure of the most common positioning tape is composed of transparent PET and acrylic glue coated on its surface. Positioning tape is generally transparent and is only pasted at a few fixed positions between the cell strings. As the photovoltaic modules become larger and larger, the positioning and bonding effect of the positioning tape is also getting worse. Especially when the POE encapsulation film is encapsulated, a large displacement will occur, resulting in unstable position between the strings, and there is a risk of short circuit caused by parallel cells.

[0004] Photovoltaic cells are usually very thin and fragile. When they are repaired, the positioning tape needs to be torn off to remove the cell. The existing positioning tape is not easy to tear off from the cell, which will damage the cell and affect the repair or recycling of the photovoltaic cell.

[0005] Since the current positioning tape has basically no reflective effect, which means it does not reflect incident light back to the photovoltaic cell, but also does not significantly enhance the light absorption or transmission efficiency. However, in certain cases, if there is unevenness or contamination on the surface of the tape, it may cause weak light scattering, which may affect the overall performance of the photovoltaic module. Summary of the invention

[0006] In order to solve the technical problems that the positioning and bonding effect of traditional positioning tapes is deteriorated, the positioning tapes are not easy to be torn off from the batteries and the positioning tapes have basically no reflective effect, the present invention proposes a photovoltaic module gap enhancement film and a preparation method and application thereof, which not only improves the positioning and bonding performance and reflectivity of the product, but also ensures the overall performance of the photovoltaic module, while at the same time, the photovoltaic module gap enhancement film can be torn off from the battery without damage to repair or recycle the photovoltaic cell.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] On the one hand, the present invention provides a photovoltaic module gap enhancement film, comprising: an adhesive layer, on which a functional layer and a composite substrate layer are arranged in sequence from bottom to top, the adhesive layer is a pressure-sensitive adhesive layer containing an activatable material, and the functional layer is a functional layer containing an ethylene copolymer with a melting point of 70-120°C.

[0009] The present invention proposes a photovoltaic module gap enhancement film and a preparation method and application thereof, which not only improves the positioning and bonding performance and reflectivity of the product, but also ensures the overall performance of the photovoltaic module. At the same time, the photovoltaic module gap enhancement film can be torn off from the battery without damage to repair or recycle the photovoltaic battery.

[0010] As a preferred technical solution, the pressure-sensitive adhesive layer of the activatable material is an incompletely coated pressure-sensitive adhesive layer to achieve a discontinuous and / or intermittent and / or zebra-coated structure or a pressure-sensitive adhesive layer with a porous structure.

[0011] As a preferred technical solution, the pressure-sensitive adhesive layer of the activatable material is a combination of one or more of polyurethane pressure-sensitive adhesive, acrylate pressure-sensitive adhesive, epoxy resin pressure-sensitive adhesive, and silicone pressure-sensitive adhesive.

[0012] As a preferred technical solution, the composite substrate layer includes the following components in parts by weight:

[0013] 67-95 parts of polymer resin A;

[0014] 5-35 parts of reflective filler;

[0015] Additives 0.1-3 parts;

[0016] The functional layer comprises the following components in parts by weight:

[0017] 72-97 parts of polymer resin B;

[0018] 3-25 parts of reflective filler;

[0019] Additives 0.1-3 parts.

[0020] As a preferred technical solution, the polymer resin A is a combination of one or more of polypropylene, polyethylene terephthalate, polyimide, polycarbonate, polyphenylene ether, polyamide, and polyethylene;

[0021] The polymer resin B is an ethylene copolymer with a melting point of 70-120° C., and the ethylene copolymer with a melting point of 70-120° C. is a combination of one or more of ethylene-butene copolymer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer, and ethylene-methacrylate copolymer;

[0022] The reflective filler is a combination of one or more of titanium dioxide, talc, calcium carbonate, barium sulfate, zinc oxide, infrared-transmitting organic pigments, infrared-reflecting inorganic pigments, and carbon black;

[0023] The additive is a combination of one or more of an antioxidant, a light stabilizer, an ultraviolet absorber, and a dispersant.

[0024] As a preferred technical solution, the activatable material in the pressure-sensitive adhesive layer is an acrylate polymer containing a tert-butoxycarbonyl group; the tert-butoxycarbonyl acrylate polymer is any one of a 2-tert-butoxycarbonylamino methyl acrylate polymer and a 3-(1-(tert-butoxycarbonyl)azetidine-2-yl) acrylic acid polymer.

[0025] As a preferred technical solution, a black coating is applied on one side of the composite substrate layer to form a black coating, and the thickness of the black coating is 5-30 um;

[0026] Or the composite substrate layer includes: a black layer and a white layer, the black layer is a black reflective filler layer, and the white layer is a white reflective filler layer.

[0027] As a preferred technical solution, the thickness of the composite substrate layer is 40-150 um, the thickness of the functional layer is 10-50 um, and the thickness of the bonding layer is 10-50 um.

[0028] In another aspect, the present invention provides a method for preparing a photovoltaic module gap enhancement film, and preparing any one of the photovoltaic module gap enhancement films described above, comprising the following steps:

[0029] S1: polymer resin A, reflective filler and additives are mixed in a certain proportion, put into a twin-screw extruder, extruded and granulated at a temperature of 100-220°C, and dried at 50-80°C for 2-5h to prepare a composite substrate layer; polymer resin B, reflective filler and additives are mixed in a certain proportion, put into a twin-screw extruder, extruded and granulated at a temperature of 100-220°C, and dried at 50-80°C for 2-5h to obtain functional layer particles;

[0030] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 100-220° C. to obtain a film with a thickness of 50-200 μm.

[0031] On the other hand, according to the use of the photovoltaic module gap synergistic film described in any one of the above in a photovoltaic module, the photovoltaic module gap synergistic film is applied between photovoltaic module cells and / or strings.

[0032] The photovoltaic module gap enhancement film provided by the present invention and its preparation method and application have the following beneficial effects:

[0033] 1) This not only improves the positioning and bonding performance and reflectivity of the product, but also ensures the overall performance of the photovoltaic module. At the same time, the photovoltaic module gap enhancement film can be torn off from the battery without damage to repair or recycle the photovoltaic cell;

[0034] 2) The adhesive layer is a pressure-sensitive adhesive layer containing an activatable material, and the functional layer is a functional layer containing an ethylene copolymer with a melting point of 70-120°C. The advantages of this design are: the pressure-sensitive adhesive layer of the activatable material provides adhesion to the battery at low temperatures to prevent the occurrence of parallel sheets and displacement before lamination; during lamination (generally lamination temperature 120-150°C), the functional layer melts and bonds the battery, while providing sufficient buffer to prevent hidden cracks and fragments of the battery;

[0035] The adhesive layer is a pressure-sensitive adhesive layer containing an activatable material. When the photovoltaic module needs to be repaired, the activatable material is activated under the heating of an infrared lamp, releasing gas, causing the adhesive force of the adhesive layer to drop instantly. In this way, the positioning film can be easily torn off the battery during repair without damaging the battery. The activatable material in the pressure-sensitive adhesive layer improves the reflectivity and interface adhesion.

[0036] 3) The pressure-sensitive adhesive layer of the activatable material is a non-completely coated pressure-sensitive adhesive layer to achieve a discontinuous and / or intermittent and / or zebra-coated structure or a pressure-sensitive adhesive layer with a porous structure. Since the present patent adopts non-complete coating of the adhesive layer, the technical effect that can be brought about is that after lamination in the laminator, the material of the functional layer melts and is more firmly combined with the battery, thereby improving the positioning and bonding performance of the product;

[0037] 4) The activatable material in the pressure-sensitive adhesive layer is an acrylate polymer containing tert-butyloxycarbonyl. The acrylate polymer containing tert-butyloxycarbonyl has high light transmittance and can be activated at 180°C-200°C to release carbon dioxide, thereby causing the adhesive layer to expand and lose its stickiness, so that the positioning film can be easily torn off during rework to complete the rework. In addition to having high light transmittance, the acrylate polymer containing tert-butyloxycarbonyl can also enhance the adhesion of the adhesive layer when added to the adhesive layer system. Existing activation materials mostly use heat-expandable microspheres, which have low light transmittance and will affect the reflection of light, resulting in reduced reflectivity. DETAILED DESCRIPTION

[0038] The preferred embodiments of the present invention are described in detail below with reference to the embodiments.

[0039] The present invention provides a gap enhancement film for a photovoltaic module, comprising: an adhesive layer, on which a functional layer and a composite substrate layer are arranged in order from bottom to top, the adhesive layer is a pressure-sensitive adhesive layer containing an activatable material, and the functional layer is a functional layer containing an ethylene copolymer with a melting point of 70-120°C.

[0040] The present invention proposes a gap enhancement film for a photovoltaic module, which has a simple process, improves the positioning and bonding performance and reflectivity of the product, ensures the overall performance of the photovoltaic module, and can simultaneously tear the gap enhancement film of the photovoltaic module from the battery without damage to repair or recycle the photovoltaic battery.

[0041] Preferably, the adhesive layer is a pressure-sensitive adhesive layer containing an activatable material, and the functional layer is a functional layer containing an ethylene copolymer with a melting point of 70-120°C. The advantages of this design are: the pressure-sensitive adhesive layer of the activatable material provides adhesion to the battery at low temperatures to prevent the occurrence of parallel sheets and displacement before lamination; during lamination (generally lamination temperature 120-150°C), the functional layer melts and bonds the battery, while providing sufficient buffer to prevent hidden cracks and fragments of the battery;

[0042] Preferably, the bonding layer is a pressure-sensitive adhesive layer containing an activatable material. When the photovoltaic module needs to be repaired, the activatable material can be activated under the heating of an infrared lamp, releasing gas, causing the adhesion of the bonding layer to drop instantly. In this way, the positioning film can be easily torn off the battery during repair without damaging the battery. The activatable material in the pressure-sensitive adhesive layer improves the reflectivity and interface adhesion.

[0043] Preferably, the pressure-sensitive adhesive layer of the activatable material is a non-completely coated pressure-sensitive adhesive layer to achieve a structure with discontinuous and / or intermittent and / or zebra-like coating or a pressure-sensitive adhesive layer with a porous structure; the pressure-sensitive adhesive layer of the activatable material is a non-completely coated pressure-sensitive adhesive layer to achieve a structure with discontinuous and / or intermittent and / or zebra-like coating or a pressure-sensitive adhesive layer with a porous structure. Since this patent adopts non-complete coating of the adhesive layer, the technical effect that can be brought about is that after lamination in the laminator, the material of the functional layer melts and is more firmly combined with the battery, thereby improving the positioning and bonding performance of the product.

[0044] Preferably, the pressure-sensitive adhesive layer of the activatable material is a combination of one or more of polyurethane pressure-sensitive adhesive, acrylate pressure-sensitive adhesive, epoxy resin pressure-sensitive adhesive, and silicone pressure-sensitive adhesive.

[0045] Preferably, the composite substrate layer comprises the following components in parts by weight:

[0046] 67-95 parts of polymer resin A;

[0047] 5-35 parts of reflective filler;

[0048] Additives 0.1-3 parts;

[0049] The functional layer comprises the following components in parts by weight:

[0050] 72-97 parts of polymer resin B;

[0051] 3-25 parts of reflective filler;

[0052] Additives 0.1-3 parts.

[0053] Preferably, the polymer resin A is a combination of one or more of polypropylene, polyethylene terephthalate, polyimide, polycarbonate, polyphenylene ether, polyamide, and polyethylene;

[0054] Preferably, the polymer resin B is an ethylene copolymer with a melting point of 70-120°C, and the ethylene copolymer with a melting point of 70-120°C is a combination of one or more of ethylene-butene copolymer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer, and ethylene-methacrylate copolymer;

[0055] Preferably, the reflective filler is a combination of one or more of titanium dioxide, talc, calcium carbonate, barium sulfate, zinc oxide, infrared-transmitting organic pigments, infrared-reflecting inorganic pigments, and carbon black;

[0056] Preferably, the additive is a combination of one or more of an antioxidant, a light stabilizer, a UV absorber, and a dispersant.

[0057] Preferably, the activatable material in the pressure-sensitive adhesive layer is an acrylate polymer containing a tert-butoxycarbonyl group; the tert-butoxycarbonyl acrylate polymer is any one of 2-tert-butoxycarbonylamino methyl acrylate polymer and 3-(1-(tert-butoxycarbonyl)azetidin-2-yl) acrylic polymer.

[0058] Preferably, one side of the composite substrate layer is coated with a black coating to form a black coating, and the thickness of the black coating is 5-30 um;

[0059] Or the composite substrate layer includes: a black layer and a white layer, the black layer is a black reflective filler layer, and the white layer is a white reflective filler layer.

[0060] Preferably, in order to realize a black photovoltaic module gap enhancement positioning film, the reflective filler in the functional layer can be one or more of infrared-transmitting organic pigments, infrared-reflective inorganic pigments, and carbon black; black paint is applied on one side of the composite substrate layer, and the black paint can be a commercially available acrylic paint, polyurethane paint, or epoxy resin paint; or the composite substrate layer can be designed as two layers, a black layer and a white layer, the black layer uses black reflective filler, and the white layer uses white reflective filler.

[0061] Preferably, the thickness of the composite substrate layer is 40-150 um, the thickness of the functional layer is 10-50 um, and the thickness of the bonding layer is 10-50 um.

[0062] The present invention provides a method for preparing a photovoltaic module gap synergistic film, and preparing any one of the photovoltaic module gap synergistic films described above, comprising the following steps:

[0063] S1: polymer resin A, reflective filler and additives are mixed in a certain proportion, put into a twin-screw extruder, extruded and granulated at a temperature of 100-220°C, and dried at 50-80°C for 2-5h to prepare a composite substrate layer; polymer resin B, reflective filler and additives are mixed in a certain proportion, put into a twin-screw extruder, extruded and granulated at a temperature of 100-220°C, and dried at 50-80°C for 2-5h to obtain functional layer particles;

[0064] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 100-220° C. to obtain a film with a thickness of 50-200 μm.

[0065] According to the application of the photovoltaic module gap synergistic film described in any one of the above in a photovoltaic module, the photovoltaic module gap synergistic film is applied between photovoltaic module cells and / or strings.

[0066] The production of the photovoltaic module shown includes the following steps:

[0067] Laying the front glass;

[0068] Laying of film;

[0069] laying batteries;

[0070] Paste the photovoltaic module gap efficiency enhancement film;

[0071] Laying of film;

[0072] Laying of back sheet or back glass;

[0073] Test EL, if there is any defect, it will be repaired, if there is no defect, it will enter the laminating machine for lamination;

[0074] In case of repair, you can use an infrared lamp to heat the location that needs repair to 180-200℃. The activatable material in the adhesive layer is activated to release carbon dioxide, and the photovoltaic module gap enhancement film at that location loses its adhesion. Tear off the photovoltaic module gap enhancement film, and re-bond the photovoltaic module gap enhancement film after the repair is completed.

[0075] Example 1

[0076] The present invention provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0077] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0078] According to the total weight, 79.4 parts of ethylene-octene copolymer of polymer resin B with a melting point of 82°C, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0079] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the composite substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0080] S3: 98.7 parts of acrylic pressure-sensitive adhesive, 1 part of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed uniformly according to the total weight to obtain an adhesive layer, and the adhesive layer is applied on one side of the functional layer obtained in step S2, and non-complete coating is achieved by zebra roller coating.

[0081] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0082] Example 2

[0083] The present invention provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0084] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0085] According to the total weight, 79.4 parts of ethylene-vinyl acetate copolymer with a melting point of 76°C of polymer resin B, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for standby use;

[0086] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0087] S3: 96.7 parts of acrylic pressure-sensitive adhesive, 3 parts of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed uniformly according to the total weight to obtain an adhesive layer, and the adhesive layer is applied on one side of the functional layer obtained in step S2, and non-complete coating is achieved by zebra roller coating.

[0088] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0089] Example 3

[0090] The present invention provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0091] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0092] According to the total weight, 79.4 parts of high molecular resin B polyethylene with a melting point of 110°C, 20 parts of reflective filler infrared permeable organic pigment, 0.1 part of antioxidant 1010, and 0.5 part of light stabilizer 2020 are mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0093] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0094] S3: 96.7 parts of polyurethane pressure-sensitive adhesive, 3 parts of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed evenly according to the total weight to obtain a bonding layer, and the bonding layer is applied on one side of the functional layer obtained in step 2, and non-complete coating is achieved by zebra roller coating.

[0095] S4: coating one side of the composite substrate layer with a black coating to form a black coating, wherein the thickness of the black coating is 5-30 um.

[0096] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0097] Example 4

[0098] The present invention provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0099] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0100] According to the total weight, 79.4 parts of ethylene-octene copolymer of polymer resin B with a melting point of 82°C, 3 parts of reflective filler infrared transparent black pigment perylene black pigment black 32, 1 part of reflective filler infrared transparent purple pigment perylene purple pigment purple 29, 0.1 part of antioxidant 1010, and 0.5 part of light stabilizer 2020 are mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0101] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0102] S3 coated a black coating on one side of the composite substrate layer. The black coating was PF850 produced by Shanghai Chengying, which was coated by a coating machine with a coating thickness of 8um.

[0103] S4: 98.7 parts of acrylic pressure-sensitive adhesive, 1 part of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed evenly, and an adhesive layer is applied on one side of the functional layer obtained in step S2, and non-complete coating is achieved by zebra roller coating.

[0104] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0105] Example 5

[0106] The present invention provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0107] S1 composite substrate layer includes a black layer and a white layer,

[0108] According to the total weight, 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talcum powder, 0.1 antioxidant 1010, and 0.5 parts of light stabilizer 2020 in the white layer of the substrate layer were mixed, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a white layer for standby use;

[0109] According to the total weight, 94.4 parts of polymer resin A polypropylene, 5 parts of reflective filler carbon black, 1 part of dispersant EBFF, 0.1 part of antioxidant 1010, and 0.5 part of light stabilizer 2020 of the substrate black layer are mixed, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a black layer for standby use;

[0110] According to the total weight, 79.4 parts of ethylene-octene copolymer of polymer resin B with a melting point of 82°C, 3 parts of reflective filler infrared transparent black pigment perylene black pigment black 32, 1 part of reflective filler infrared transparent purple pigment perylene purple pigment purple 29, 0.1 part of antioxidant 1010, and 0.5 part of light stabilizer 2020 are mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0111] S2: In step 1, the white layer, black layer and functional layer particles are obtained, and put into a multi-layer casting extruder. At a temperature of 200° C., a film with a thickness of 120 μm is cast, wherein the black layer of the substrate has a thickness of 20 μm, the white layer has a thickness of 70 μm, and the functional layer has a thickness of 30 μm.

[0112] S3: 98.7 parts of acrylic pressure-sensitive adhesive, 1 part of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed evenly to obtain an adhesive layer, and the adhesive layer is coated on one side of the functional layer obtained in step S2, and non-complete coating is achieved by zebra roller coating.

[0113] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0114] Comparative Example 1

[0115] Comparative Example 1 provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0116] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0117] According to the total weight, 79.4 parts of ethylene-octene copolymer of polymer resin B with a melting point of 82°C, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0118] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0119] S3: 99.7 parts of acrylic pressure-sensitive adhesive and 0.3 parts of ultraviolet absorber UV3035 are mixed uniformly according to the total weight to obtain an adhesive layer, and the adhesive layer is coated on one side of the functional layer obtained in step S2, and non-complete coating is achieved by zebra roller coating.

[0120] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0121] Comparative Example 2

[0122] Comparative Example 2 provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0123] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0124] According to the total weight, 79.4 parts of ethylene-octene copolymer of polymer resin B with a melting point of 82°C, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0125] S2: In step 1, the substrate layer and the functional layer particles are obtained, and the particles are put into a multi-layer casting extruder. At a temperature of 200° C., a film with a thickness of 120 μm is cast, wherein the thickness of the substrate layer is 90 μm and the thickness of the functional layer is 30 μm.

[0126] S3: 96.15 parts of acrylic pressure-sensitive adhesive, 1 part of heat-expandable microspheres, and 0.1 parts of ultraviolet absorber UV3035 are mixed uniformly according to the total weight to obtain an adhesive layer, and the adhesive layer is applied on one side of the functional layer obtained in step S2, and non-complete coating is achieved by zebra roller coating.

[0127] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0128] Comparative Example 3

[0129] Comparative Example 3 provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0130] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0131] According to the total weight, 79.4 parts of ethylene-octene copolymer of polymer resin B with a melting point of 82°C, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for use;

[0132] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0133] S3: 98.7 parts of acrylic pressure-sensitive adhesive, 1 part of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed evenly to obtain an adhesive layer, and the adhesive layer is completely coated on one side of the functional layer obtained in step S2.

[0134] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0135] Comparative Example 4

[0136] Comparative Example 4 provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0137] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0138] According to the total weight, 79.4 parts of ethylene-vinyl acetate copolymer with a melting point of 65°C of polymer resin B, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion granulation, and dried at 50°C for 5h to obtain functional layer particles for standby use;

[0139] S2: In step 1, the composite substrate layer and functional layer particles are obtained, and put into a multi-layer casting extruder. At a temperature of 200° C., a film with a thickness of 120 μm is cast, wherein the substrate layer is 90 μm thick and the functional layer is 30 μm thick.

[0140] S3: 98.7 parts of acrylic pressure-sensitive adhesive, 1 part of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed evenly to obtain an adhesive layer, and the adhesive layer is applied on one side of the functional layer obtained in step 2 by zebra-type roller coating to achieve incomplete coating.

[0141] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0142] Comparative Example 5

[0143] Comparative Example 5 provides a method for preparing a photovoltaic module gap enhancement film, comprising the following steps:

[0144] S1: 69.4 parts of polymer resin A polypropylene, 25 parts of reflective filler titanium dioxide, 5 parts of reflective filler talc, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 are mixed according to the total weight, put into a twin-screw extruder at a temperature of 200°C for extrusion granulation, and dried at 80°C for 5h to obtain a composite substrate layer for standby use;

[0145] According to the total weight, 79.4 parts of high molecular resin B polyethylene with a melting point of 125°C, 20 parts of reflective filler titanium dioxide, 0.1 parts of antioxidant 1010, and 0.5 parts of light stabilizer 2020 were mixed, put into a twin-screw extruder at a temperature of 120°C for extrusion and granulation, and dried at 50°C for 5h to obtain a functional layer for standby use;

[0146] S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 200° C. to obtain a film with a thickness of 120 μm, wherein the substrate layer has a thickness of 90 μm and the functional layer has a thickness of 30 μm;

[0147] S3: 98.7 parts of acrylic pressure-sensitive adhesive, 1 part of activatable material 2-tert-butyloxycarbonylamino methyl acrylate polymer, and 0.3 parts of ultraviolet absorber UV3035 are mixed evenly to obtain an adhesive layer, and the adhesive layer is applied on one side of the functional layer obtained in step 2 by zebra roller coating to achieve non-complete coating.

[0148] The present invention provides a photovoltaic module gap synergistic film, which is prepared according to the above method.

[0149] Comparative Example 6

[0150] Commercially available positioning tape.

[0151] Experimental means of experimental data testing

[0152] The following tests were performed on Examples 1-5 and Comparative Examples 1-6:

[0153] The reflectivity is tested according to IEC62788-2-1, and the test band is 380-1100nm.

[0154] The method for testing the adhesion to the battery is to cut the sample into 1cm wide strips, paste them on the battery, and use a tensile machine to test the peel strength with the battery. The adhesion to the battery after lamination is to put the glass / encapsulation film / battery / positioning film / release paper into the laminator from bottom to top for lamination, the lamination temperature is 120℃ for the first chamber and 140℃ for the second chamber, the lamination time is 18min, and the peel strength with the battery is tested with a tensile machine after lamination.

[0155] The adhesion after activation is measured by pasting a 1 cm strip onto the battery, then irradiating it with an infrared lamp at 180°C for 10″, and then testing the peel strength from the battery. After irradiation with the infrared lamp, the activation material in the embodiment is activated, so that the positioning film can be easily torn off during repair, and the battery will not be damaged when the positioning film is torn off.

[0156] The samples of Examples 1-5 and Comparative Examples 1-6 were cut into 0.5 cm strips and pasted between module sheets and strings. With other materials unchanged, modules were prepared and the module power was tested.

[0157] The experimental data test results are shown in Table 1.

[0158] Table 1 Experimental data test results

[0159]

[0160]

[0161] From the data in Table 1, it can be seen that the reflectivity of Examples 1-3 is above 91%, while the reflectivity of Comparative Example 2, which adds traditional heat-expandable microsphere activation material, is only 82.46%, indicating that the addition of heat-expandable microspheres will affect the reflectivity. Comparative Example 6 is a commercially available positioning tape, which is a light-transmitting material and has basically no reflective effect.

[0162] The adhesion between Examples 1-3 and Comparative Example 1 before lamination is significantly higher than that of Comparative Example 1 without adding activation material, indicating that the addition of tert-butyloxycarbonyl acrylate polymer material of the present patent can improve the adhesion performance of the pressure-sensitive adhesive layer.

[0163] Comparing the bonding strength between Examples 1-3 and Comparative Examples 3 and 6 after lamination, the data are significantly higher than those of Comparative Examples 3 and 6. This is because the present invention adopts incomplete coating of the bonding layer, which can bring the technical effect that after lamination in the laminator, the material of the functional layer melts and the bonding with the battery is more firmly. However, in Comparative Example 3 where the bonding layer is completely coated, the functional layer cannot be bonded to the battery. Comparative Example 6 has no functional layer, so the bonding strength with the battery does not change after lamination.

[0164] Photovoltaic cells are usually very thin and fragile, and the positioning tape needs to be torn off to remove the cells during repair. In the embodiments of this patent, activatable materials are added. Under the heating of infrared lamps, the activation materials are activated and release gas, which causes the adhesion of the adhesive layer to drop instantly. In this way, the positioning film can be easily torn off the cells during repair without damaging the cells. After irradiation with infrared lamps at 180°C for 10″, the adhesion of Examples 1-3 dropped to 0.5N / cm or less, and they were easily torn apart. Comparative Examples 1 and 6 without adding activation materials had no activation effect.

[0165] Power comparison is positively correlated with reflectivity. The photovoltaic module gap enhancement films provided in Examples 1-3 are applied to photovoltaic modules with higher power than Comparative Examples 2 and 6. The photovoltaic module of Comparative Example 4 has jagged and flanging phenomena on its appearance, which is due to the low melting point of the functional layer, resulting in poor appearance caused by the flow of the functional layer during lamination; Comparative Example 5 has hidden cracks in the battery, which is due to the high melting point of the functional layer, which does not play a buffering role during lamination, thus damaging the battery.

[0166] Examples 4 and 5 are black synergistic positioning film solutions, which are applied to black photovoltaic modules. It can be seen that the law of their adhesion is the same as that of Examples 1-3, indicating that the solutions using black photovoltaic modules have the same implementation effect.

[0167] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all various changes or equivalent substitutions falling within the scope of the claims of the present application are included. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present invention.

Claims

1. A gap enhancement film for a photovoltaic module, characterized in that: include: The adhesive layer comprises a functional layer and a composite substrate layer in sequence from bottom to top, the adhesive layer is a pressure-sensitive adhesive layer containing an activatable material, and the functional layer is a functional layer containing an ethylene copolymer with a melting point of 70-120°C.

2. The gap enhancement film of the photovoltaic module according to claim 1, characterized in that: The pressure-sensitive adhesive layer of the activatable material is a non-completely coated pressure-sensitive adhesive layer so as to realize a discontinuous and / or intermittent and / or zebra-coated structure or a pressure-sensitive adhesive layer with a porous structure.

3. The gap enhancement film of the photovoltaic module according to claim 1 or 2, characterized in that: The pressure-sensitive adhesive layer of the activatable material is a combination of one or more of polyurethane pressure-sensitive adhesive, acrylate pressure-sensitive adhesive, epoxy resin pressure-sensitive adhesive, and silicone pressure-sensitive adhesive.

4. The gap enhancement film of the photovoltaic module according to claim 1, characterized in that: The composite substrate layer comprises the following components in parts by weight: 67-95 parts of polymer resin A; 5-35 parts of reflective filler; Additives 0.1-3 parts; The functional layer comprises the following components in parts by weight: 72-97 parts of polymer resin B; 3-25 parts of reflective filler; Additives 0.1-3 parts.

5. The gap enhancement film of the photovoltaic module according to claim 4, characterized in that: The polymer resin A is a combination of one or more of polypropylene, polyethylene terephthalate, polyimide, polycarbonate, polyphenylene ether, polyamide, and polyethylene; The polymer resin B is an ethylene copolymer with a melting point of 70-120° C., and the ethylene copolymer with a melting point of 70-120° C. is a combination of one or more of ethylene-butene copolymer, ethylene-octene copolymer, ethylene-vinyl acetate copolymer, and ethylene-methacrylate copolymer; The reflective filler is a combination of one or more of titanium dioxide, talc, calcium carbonate, barium sulfate, zinc oxide, infrared-transmitting organic pigments, infrared-reflecting inorganic pigments, and carbon black; The additive is a combination of one or more of an antioxidant, a light stabilizer, an ultraviolet absorber, and a dispersant.

6. The gap enhancement film for photovoltaic modules according to any one of claims 1 to 2, characterized in that: The activatable material in the pressure-sensitive adhesive layer is an acrylate polymer containing a tert-butyloxycarbonyl group; the tert-butyloxycarbonyl acrylate polymer is any one of a 2-tert-butyloxycarbonylamino methyl acrylate polymer and a 3-(1-(tert-butyloxycarbonyl)azetidin-2-yl) acrylic acid polymer.

7. The gap enhancement film of a photovoltaic module according to claim 1, characterized in that: One side of the composite substrate layer is coated with a black coating to form a black coating, wherein the thickness of the black coating is 5-30 um; Or the composite substrate layer includes: a black layer and a white layer, the black layer is a black reflective filler layer, and the white layer is a white reflective filler layer.

8. The gap enhancement film of a photovoltaic module according to claim 1, characterized in that: The thickness of the composite substrate layer is 40-150 um, the thickness of the functional layer is 10-50 um, and the thickness of the bonding layer is 10-50 um.

9. A method for preparing a photovoltaic module gap enhancement film, characterized in that: The photovoltaic module gap enhancement film according to any one of claims 1 to 8 is prepared, comprising the following steps: S1: polymer resin A, reflective filler and additives are mixed in a certain proportion, put into a twin-screw extruder, extruded and granulated at a temperature of 100-220°C, and dried at 50-80°C for 2-5h to prepare a composite substrate layer; polymer resin B, reflective filler and additives are mixed in a certain proportion, put into a twin-screw extruder, extruded and granulated at a temperature of 100-220°C, and dried at 50-80°C for 2-5h to obtain functional layer particles; S2: The composite substrate layer and functional layer particles obtained in step 1 are put into a multi-layer casting extruder, and cast at a temperature of 100-220° C. to obtain a film with a thickness of 50-200 μm.

10. Use of the photovoltaic module gap enhancement film according to any one of claims 1 to 8 in a photovoltaic module, wherein the photovoltaic module gap enhancement film is applied between photovoltaic module cells and / or strings.

Citation Information

Cited By

  • Black resin composition, molded articles and laminates

    JP2026102474A

  • Black resin composition, molded article, and multilayer body

    WO2026126785A1